Fundamentals of Electronic Systems Design - Lienig, Jens.; Bruemmer, Hans.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This textbook covers the design of electronic systems from the ground up, from drawing and CAD essentials to recycling requirements. Chapter by chapter, it deals with the challenges any modern system designer faces: The design process and its fundamentals, such as technical drawings and CAD, electronic system levels, assembly and packaging issues and appliance protection classes, reliability analysis, thermal management and cooling, electromagnetic compatibility (EMC), all the way to recycling requirements and environmental-friendly design principles. For Slides and Other Information: https://www.ifte.de/books/esd/index.html "This unique book provides fundamental, complete, and indispensable information regarding the design of electronic systems. This topic has not been addressed as complete and thorough anywhere before. Since the authors are world-renown experts, it is a foundational reference for today's design professionals, as well as for the next generation of engineering students." Dr. Patrick Groeneveld, Synopsys Inc.
Introduction -- Design Process and its Fundamentals -- System Architecture and Protection Requirements -- Reliability Analysis -- Thermal Management and Cooling -- Electromagnetic Compatibility (EMC) -- Recycling Requirements and Design for Environmental Compliance -- Appendix.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Logic design; Electronic Circuits and Systems; Processor Architectures; Logic Design